Inducing consumers to use calorie information: a multinational investigation. Issue 4 (3rd April 2023) - Oh, Ga-Eun (Grace); Huh, Young Eun; Mukhopadhyay, Anirban
Abstract: Objective: We identify individuals who set daily intake budgets and examine if an intervention making people estimate their calorie intake up to a certain point in the day helps those setting daily budgets to regulate their calorie intake for the remainder of the day, after high prior consumption. Design: We conducted an online experiment in five countries: Australia, China, Germany, India, and the UK (n = 3, 032) using a 2 (setting calorie budget: yes vs. no, measured) x 2 (intervention: intake reminder vs. control, manipulated) between-subjects design, with the amount of prior consumption measured. Participants were contacted in the afternoon. Those in the intervention condition were asked to estimate their prior calorie intake on that day. Main outcome measures: We measured the individual characteristics of those who set daily calorie budgets and the intended calorie intake for the remainder of the day. Results: Among people who set daily calorie budgets, the intervention reduced intended calorie intake for the remainder of the day by 176 calories if they had already consumed a high amount of calories that day. Conclusion: A timely intervention to estimate one's calorie intake can lower additional intended calorie intake among those who set daily calorie budget.